The effect of carbohydrate mouth rinse on 1-h cycle time trial performance - Carter, J. M.; Jeukendrup, A. E.; Jones, D. A. (Medicine & Science in Sports & Exercise, 2004)
Purpose and Method: To investigate the possible role of carbohydrate (CHO) receptors in the mouth in influencing exercise performance, seven male and two female endurance cyclists ([latin capital V with dot above]O2max 63.2 +/- 2.7 (mean +/- SE) mL[middle dot]kg-1[middle dot]min-1) completed two performance trials in which they had to accomplish a set amount of work as quickly as possible (914 +/- 40 kJ). On one occasion a 6.4% maltodextrin solution (CHO) was rinsed around the mouth for every 12.5% of the trial completed. On the other occasion, water (PLA) was rinsed. Subjects were not allowed to swallow either the CHO solution or water, and each mouthful was spat out after a 5-s rinse.